PARENTAL ATTITUDES OF MOTHERS LIVING IN FAMILIES WITH/WITHOUT THE PROBLEM OF AGGRESSION AND VIOLENCE - Przybysz - Zaremba, Małgorzata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The text is based on its empirical foundations; it concerns the parental attitudes assumed by mothers living in families with the problem of aggression and violence and these that do not experience such a problem. The research was conducted among 710 women bringing up children of different ages. The aim of the study was to answer the following question: What parental attitudes towards children are taken by the mothers living in families where there is a problem of aggression and violence, or lack thereof ?. The study used two tools: the scale of family attitudes according to Maria Braun-Gałkowska and the questionnaire of own authorship. The data elements used to develop the obtained results were, among others, Chi² test and Vxy-Cramer coefficients.